Card night : classic games, classic decks, and the history behind them, 52 Games for all ages - Roya, Will (Black Dog & Leventhal Publishers, 2021)
"Learn when to hold 'em and when to fold 'em with Card Night, a compendium of 52 classic card games, including Hearts and Bridge, Rummy and Go Fish. At various points in history, playing cards were also used as currency, tools for propaganda, and even as a means for sending coded messages. In addition to providing the rules of standard game play, Card Night also details the fascinating stories and peculiarities behind some of the world's most famous card decks"--